Vegetative rescue of Cedrela fissilis Vell. by the rooting of cuttings from epicormic and canopy sprouts - Cezário Ferreira dos Santos Junior; Tássio Dresch Rech; Marcio Carlos Navroski; Pedro Boff; Mari Inês Carissimi Boff (Ciência Rural, 2021)
ABSTRACT: Cedrela fissilis is a species of great genetic diversity, with low population density and seminal propagation, which causes difficulties in the vegetative propagation process. This research evaluated the vegetative rescue and propagation of stem cutting rooting originated from epicormic and canopy sprouts of C. fissilis. For this, the induction of epicormic sprouts was evaluated 52 days after the complete girdling and semi-girdling 20 and 40 cm from the ground, and no girdling treatment, during spring (2018), summer (2018) and autumn (2019). The variables evaluated were, survival (%), sprouting (%), number, length (cm) and diameter (mm) of sprouts. The cuttings were made from spring epicormic sprouts, divided in two categories: 10 cm cuttings placed vertically in pits and 5 cm cuttings placed horizontally in furrows. The canopy sprouts were collected in the summer, then cut in apical and intermediate cuttings (15 cm). After 60 days, the cuttings were evaluated in survival (%), rooting (%), callus (%), average number and length of roots (cm). Results showed that only the complete girdling produced sprouts (average >67%) with no difference between 20 and 40 cm heights, with a greater number of sprouts during spring. The cuttings from epicormic sprouts, planted vertically in pits presented higher percentage of rooting (44%) than cuttings planted horizontally in furrows (17%). Cuttings from the canopy had inconsiderable rooting (apical - 2%; intermediate - 0%). The girdling periods influences the number of epicormic sprouts and its use for cutting was more efficient in rooting.